Enhancing Early Literacy Skills Through Play-Based Learning Activities at RA Nurul Yaqin: A Classroom Action Research - Linda Afiyani; Jannati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of play-based learning activities in enhancing early literacy skills at RA Nurul Yaqin. The study was conducted with a group of kindergarten students, aged 5-6 years, who were provided with interactive and engaging activities designed to stimulate language development. The primary objective of this research was to determine whether play-based activities could improve children's ability to recognize letters, understand phonemic sounds, and develop a basic vocabulary. The research was implemented in two cycles, with each cycle consisting of planning, action, observation, and reflection. The play-based activities incorporated various hands-on, creative tasks such as storytelling, singing, letter recognition games, and role-playing. Data were collected through direct observation, teacher journals, and student assessments before and after the intervention. The findings of this study revealed significant improvements in students' literacy skills, particularly in their ability to recognize letters and their phonetic awareness. Moreover, the students showed increased enthusiasm and engagement in the learning process. This research highlights the potential of integrating play into early childhood education, suggesting that play-based learning not only fosters a positive learning environment but also accelerates literacy development in young learners. It is recommended that RA Nurul Yaqin and other similar institutions adopt play-based approaches to strengthen the foundation of early literacy among preschool-aged children.